The Fascists Are Coming! Teacher Education for When Right-Wing Activism Micro-Governs Classroom Practice - Peter Appelbaum (MDPI AG, 2023)
U.S. educational reform is often the harbinger of global demands on mathematics education practices globally. It behooves teacher education to 'catch up' on current trends, hopefully, to stave off the worst of the fascist tendencies of contemporary politics of education. Past foci on research-based 'best practices' and 'mathematics for all', grounded in liberal multiculturalism (confirming expectations from critical mathematics education scholarship), have become the targets of activists and politicians, turning once-exemplary teachers and their students into casualties. The four phases of currere are employed to study this phenomenon and to identify strategies and tactics for teacher education programs. The currere methodology indicates that the content of such programs must reduce time devoted to evidence and research-based practice in order to accommodate techniques and knowledge bases for the recognition of right-wing tactics, clowning, slogan parody, and political organizing. Teacher education must further place mathematics teachers' embrace of expertise, authority, and neutrality within broader perspectives on the politics of education, organizational infrastructure strategies and tactics, resource curation, and personal safety planning. Teacher educators themselves must prepare responses to threats on their careers, lives, and families, and proactive 'game plans' for the development of new program curricula.